2010
DOI: 10.1039/c0pp00059k
|View full text |Cite
|
Sign up to set email alerts
|

Independence and inverted dependence on temperature of rates of photoinduced electron transfer in double-linked phthalocyanine-fullerene dyads

Abstract: Photoinduced electron transfer reactions of phthalalocyanine-fullerene dyads, in which donor and acceptor moieties are covalently linked to each other, with one or two malonic linkers, were studied. In the dyads with two linkers, phthalocyanine and fullerene have mutual orientations, face-to-face or face-to-tail, which differ from each other and influence photoinduced electron transfer processes. Quantitative spectroscopic and time-resolved spectroscopic measurements were done in polar and non-polar solvents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…The time‐resolved spectrum at a delay time of 1 ps has roughly half of the intensity of the spectrum right after excitation (at 0 ps) in the Q‐band region. However, the bleaching increases again with the 15 ps time constant and at the same time a band is formed at 930 nm, which is a typical feature of a Pc cation 13. Also, a sub‐band at 1020 nm is seen at a delay time of 50 ps, which is attributed to the azafullerene anion 9.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The time‐resolved spectrum at a delay time of 1 ps has roughly half of the intensity of the spectrum right after excitation (at 0 ps) in the Q‐band region. However, the bleaching increases again with the 15 ps time constant and at the same time a band is formed at 930 nm, which is a typical feature of a Pc cation 13. Also, a sub‐band at 1020 nm is seen at a delay time of 50 ps, which is attributed to the azafullerene anion 9.…”
Section: Resultsmentioning
confidence: 92%
“…Pump–probe measurements of C 59 N–Pc dyad 4 were carried out by using excitations at 400 and 600 nm. The transient absorption response of C 59 N–Pc was more complex than that of C 60 –Pc,13 despite the close resemblance of the two dyads. A global multi‐exponential fitting was applied to the transient absorption measurements of the dyad and at least a four‐exponential fit model had to be applied to obtain a reasonable approximation of the experimental data, according to standard criteria—minimal sigma value and random residual distribution.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In benzonitrile, the formation of the charge‐separated state dominates in deactivation, but the main pathway is again a multistep one, in which energy transfer precedes electron transfer (C 59 N–Pc 1S →C 59 N 1S –Pc→C 59 N .− –Pc ⋅+ ). A comparison of the above‐mentioned results of 28 with those of a previously reported C 60 –Pc dyad revealed that the lower energy of C 59 N 1S compared to that of C 60 1S explained the ease of energy transfer in 28 even in benzonitrile—that is to say that C 59 N 1S –Pc lies energetically lower than C 59 N–Pc 1S , while the opposite goes for C 60 –Pc. Thus, although the lifetimes of the charge‐separated states of 28 and C 60 –Pc in benzonitrile were comparable (190 and 320 ps respectively), the much slower electron‐transfer process in 28 (15 ps) compared to C 60 –Pc (2 ps), is attributed to the extra step of energy transfer.…”
Section: Indirect Functionalizationmentioning
confidence: 73%
“…In benzonitrile,t he formation of the charge-separated state dominates in deactivation, but the main pathwayi sa gain am ultistep one, in which energy transfer precedes electron transfer (C 59 N-Pc 1S !C 59 N 1S -Pc!C 59 NC À -Pc ·+ ). Ac omparison of the above-mentioned results of 28 with those of ap reviouslyr eported C 60 -Pc dyad [23] revealed that the lower energy of C 59 N 1S comparedt ot hat of C 60 1S explained the easeo fenergy transfer in 28 even in benzonitrile-that is to say that C 59 N 1S -Pc lies energetically lower than C 59 N-Pc 1S ,w hilet he opposite goes for C 60 -Pc. Thus, althought he lifetimes of the charge-separated states of 28 and C 60 -Pc in benzonitrile were comparable (190 and 320 ps respectively), the much slower electron-transfer process in 28 (15 ps) compared to C 60 -Pc (2 ps), is attributed to the extra step of energy transfer.…”
Section: Indirect Functionalizationmentioning
confidence: 78%